Polymer-supported palladium-imidazole complex catalyst for hydrogenation of substituted benzylideneanilines - Udayakumar, V.; Alexander, S.; Gayathri, V.; Shivakumaraiah; Patil, K. R.; Viswanathan, B. (Journal of Molecular Catalysis A-Chemical, 2010)
The polymer-supported palladium-imidazole complex catalyst was synthesized and characterized by various techniques Such as elemental analysis, IR spectroscopy and TG analysis. The physico-chemical properties such as bulk density, Surface studies by BET method and swelling studies of catalyst in different solvents were investigated. XPS Studies were carried out to identify the oxidation state of palladium in the catalyst. The morphology of the support and the catalyst was studied using scanning electron microscope. Using the synthesized catalyst, hydrogenation of benzylideneaniline and a few of its para Substituted derivatives was carried out at ambient conditions. The influence of variation in temperature, concentration of the catalyst as well as the substrate on the rate of reaction Was Studied. The catalyst showed an excellent recycling efficiency over six cycles without leaching of metal from the polymer support. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Benzylideneaniline; Hydrogenation; kinetics; Polymer-supported palladium-imidazole complex catalyst

Synthesis, characterisation of polymer-supported palladium-2-methylimidazole complex catalyst for the hydrogenation of aromatic nitro compounds - Velua, Udayakumar; Stanislaus, Alexander; Virupaiah, Gayathri; Shivakumaraiah; Patil, Kashinath Rangu; Balasubramanian, Viswanathan (Journal of Chemical Research, 2011)
A polymer-supported palladium-2-methylimidazole complex was synthesised and characterised by various physicochemical methods. The complex was successfully used as a catalyst for the hydrogenation of nitrobenzene and a few of its derivatives under ambient conditions. Results reveal that the electronic as well as the steric effects of the substitutent control the rate of hydrogenation of the nitro group in the studied nitro compounds. The kinetics of hydrogenation and the reusability of the catalyst were also studied.
Keywords: aromatic nitro compounds; Hydrogenation; polymer-supported complex catalyst; transition metal complexes